Diagnostic Accuracy of Chest X-Ray in Interstitial Lung Diseases, Keeping High Resolution Computed Tomography Scan as Gold Standard - Khadeeja Anwar; Ummara Siddique; Irfanullah Khan; Abdullah Safi; Hadia Abid; Ayesha Anwar; Karishma Israr (Gandhara University, 2023)
OBJECTIVES To determine the accuracy of the plain chest radiograph in diagnosing interstitial lung diseases (ILDs), keeping a high-resolution CT scan (HRCT) as the gold standard. METHODOLOGY A cross-sectional study was conducted. A total of 75 patients who visited the Department of Radiology department over two years were assessed by prospective analysis of their radiology reports. All the HRCTs and Chest X-ray images were reviewed. Data collected was recorded on a specially designed proforma and entered into Microsoft Excel and SPSS (Version 22.0. IBM Corp., Armonk, NY). Patients with a history of acute exacerbation of symptoms were excluded. RESULTS The median age of the patients was 59 years, with SD 12.2. Chest radiographs detected interstitial lung disease (ILD) in 42/75 (56%).). The chest radiograph's sensitivity, specificity, Positive Predictive Value (PPV), and Negative Predictive Value (NPV) were 76%, 84%, 86.3% and 76.7%. A plain chest X-ray's positive likelihood ratio (LR+) was 4.75, while the negative likelihood ratio (LR-) was 0.28. The overall accuracy of CXR was calculated as 78.6%. CONCLUSION Our study concluded that chest X-ray is the ideal initial investigation for diagnosing Interstitial lung disease (ILDS) with an accuracy of 78.6% compared to HRCT.